Prostate cancer survivors: risk and mortality in second primary cancers - Chattopadhyay, Subhayan; Zheng, Guoqiao; Hemminki, Otto; Försti, Asta; Sundquist, Kristina; Hemminki, Kari (Cancer medicine, 2018)
To assess etiological and clinical consequences of second primary cancers (SPCs) in prostate cancer (PC) patients, we followed newly diagnosed patients to identify men who were diagnosed with a SPC and recorded their causes of death. We used the Swedish Family-Cancer Database to assess relative risks (RRs) and causes of death in SPCs until the year 2015 in patients with a PC diagnosis between 2001 and 2010. Among a total of 4.26 million men, 76 614 were diagnosed with PC at the median age of 71 years. Among them, 8659 (11.3%) received a subsequent diagnosis of SPC after a median follow-up of 4 years. The most common SPCs were colorectal, skin, bladder, and lung cancers, melanoma, and non-Hodgkin lymphoma. The ranking was almost identical with first cancers among elderly men in Sweden. The RR for SPCs in prostate-specific antigen—detected PC was approximately equal to RR in other PC. Mortality patterns of PC patients were distinct depending on the presence or absence of SPC. Among patients with SPC, 47.8% died as a result of the corresponding SPC, followed by other causes (22.2%) and PC (18.1%). For patients without SPC, PC and non-neoplastic causes almost matched each other as the main causes of death (48.5% and 47.8%). The results suggest that SPCs appear autonomous from primary PC and reflect incidence and mortality of first cancers in general. SPC was the most common cause of death in patients with SPC; close to half of the patients died due to SPC. For improved survival in PC patients, prevention and early detection of SPCs would be important, and the present results suggest that risk factors for SPC in PC are the same as those for first cancer in general.
Gesehen am 26.08.2020